2015
DOI: 10.1039/c4an01985g
|View full text |Cite
|
Sign up to set email alerts
|

The pituitary gland under infrared light – in search of a representative spectrum for homogeneous regions

Abstract: The pituitary gland is a small but vital organ in the human body. It is located at the base of the brain and is often described as the master gland due to its multiple functions. The pituitary gland secretes and stores hormones, such as the thyroid-stimulating hormone (TSH), adrenocorticotropic hormone (ACTH), growth hormone (hGH), prolactin, gonadotropins, and luteinizing hormones, as well as the antidiuretic hormone (ADH). A proper diagnosis of pituitary disorders is of utmost importance as this organ partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…A related technique to Raman spectroscopy is Fourier transform infrared (FT-IR) spectroscopy [19] which has been applied to pituitary gland and pituitary adenoma by Banas et al [20] and Steiner et al [21]. These studies demonstrated the feasibility of FT-IR to provide diagnostic findings, however, detailed information for different pituitary adenoma types is yet to be shown.…”
Section: Introductionmentioning
confidence: 99%
“…A related technique to Raman spectroscopy is Fourier transform infrared (FT-IR) spectroscopy [19] which has been applied to pituitary gland and pituitary adenoma by Banas et al [20] and Steiner et al [21]. These studies demonstrated the feasibility of FT-IR to provide diagnostic findings, however, detailed information for different pituitary adenoma types is yet to be shown.…”
Section: Introductionmentioning
confidence: 99%
“…Current clinical methodologies for body fluid profiling rely on quantitative parameters with set thresholds to distinguish between normal and abnormal conditions. 16 Hyper-cluster analysis of image data from biopsy sections is becoming equivalent to pathological assessments, [17][18][19] whereas…”
Section: Introductionmentioning
confidence: 99%
“…40 The anti-NSE antibody-coated electrode exhibited broad and intense peaks at 1645 cm −1 (amide I) and 1546 cm −1 (amide II). 41 These amide bands were signs of anti-NSE immobilization (Fig. 1, purple).…”
Section: Resultsmentioning
confidence: 96%